The relationship between actual motor competence and physical activity in children: mediating roles of perceived motor competence and health-related physical fitness. Issue 16 (17th August 2016) - Khodaverdi, Zeinab; Bahram, Abbas; Stodden, David; Kazemnejad, Anoshirvan
ABSTRACT: The purpose of this study was to investigate whether perceived motor competence and components of health-related physical fitness mediated the relationship between actual motor competence and physical activity in 8- to 9-year-old Iranian girls. A convenience sample of 352 girls (mean age = 8.7, SD = 0.3 years) participated in the study. Actual motor competence, perceived motor competence and children's physical activity were assessed using the Test of Gross Motor Development-2, the physical ability sub-scale of Marsh's Self-Description Questionnaire and Physical Activity Questionnaire for Older Children, respectively. Body mass index, the 600 yard run/walk, curl-ups, push-ups, and back-saver sit and reach tests assessed health-related physical fitness. Preacher & Hayes (2004) bootstrap method was used to assess the potential mediating effects of fitness and perceived competence on the direct relationship between actual motor competence and physical activity. Regression analyses revealed that aerobic fitness ( b = .28, 95% CI = [.21, .39]), as the only fitness measure, and perceived competence ( b = .16, 95% CI = [.12, .32]) were measures that mediated the relationship between actual motor competence and physical activity with the models. Development of strategies targeting motor skill acquisition, children's self-perceptions of competence and cardiorespiratory fitness should be targeted to promote girls' moderate-to-vigorous physical activity.